Nepal : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Nepal. (IMF Staff Country Reports; Country Report ;, 2020)
This paper presents Nepal's Request for Disbursement Under the Rapid Credit Facility (RCF). The coronavirus disease 2019 pandemic is having a severe impact on Nepal's economy. During recent months, remittances have fallen considerably, tourist arrivals collapsed, and domestic activity has taken a hit amid social distancing measures. The authorities are taking proactive, well-targeted measures to address the human and economic impact of the pandemic, while preserving macroeconomic stability. Such measures include increasing health spending, strengthening social assistance to protect the most vulnerable, and providing bank liquidity and credit support. Additional assistance from development partners, beyond what had already been committed before the outbreak of the pandemic, is needed to close the remaining balance of payments gap and ease the fiscal situation. The authorities' commitment to high standards of transparency and governance in the management of financial assistance is welcome. The IMF staff assesses that Nepal meets the RCF eligibility requirements and supports the request. Public debt is at low risk of distress and there is adequate capacity to repay the Fund. The IMF disbursement is expected to play a catalytic role in securing additional financing from Nepal's development partners.